OUTDOOR AIR TEMPERATURE, THERMAL COMFORT, HEALTH AND PERFORMANCE AT A BUILDING CONSTRUCTION SITE IN ABUJA, NIGERIA (Proceedings of the International Conference on Public Health, 2022)
Results from previous research shows that high outdoor air temperature can bedetrimental to thermal comfort, health and productivity. However, are the resultsapplicable to building construction workers in Nigeria? In view of this question, this studyinvestigated the effect of outdoor air temperature on the thermal comfort, health andperformance of a sample of Sandcrete block layers at a building construction site in Abuja,Nigeria. The study involved literature review and a field experiment. The field experimentexamined the thermal comfort, health and performance of a sample Sandcrete block layersat LT 28.50C and HT 37.010C. (LT) and (HT) are the lowest and highest naturallyoccurring outdoor air temperatures in the construction site during the study. Paired t-testand Wilcoxon-signed ranked test was used to analyse the data from the field experiment.Result from analysis of data shows that: the thermal comfort of the samples wassignificantly affected at HT 37.010C in comparison to LT 28.50C. Also core bodytemperature significantly increased at HT 37.010C in comparison LT 28.50C. Furthermore,sensation of skin burn, fatigue and negative mood significantly increased at HT 37.010C incomparison LT 28.50C. No significant change in symptoms of headache and dizziness wasobserved. Lastly, performance of the sandcrete block was slightly low at HT 37.010C incomparison to LT 28.50C. The conclusion from this study is that, high outdoor temperature(37.010C) is detrimental to the thermal comfort, health and performance sandcrete blocklayers in Nigeria. The result from this study complements the findings of another relatedresearch. Broadly, results from this study provides empirical data that may stimulatestrategies of mitigating the effect of high outdoor air temperature on the thermal comfort,health and performance of workers during high outdoor temperatures at construction sitesin Nigeria.
Keywords: thermal comfort, health, productivity, outdoor air temperature, field experiment